Internationalisation of Turkish law enforcement: a study of anti-drug trafficking - Çevik, Kürşat (2013)
This thesis explains how policing has changed in Turkey between the late 1960s and 2012 and explores ways to explain the changes by looking at the enforcement anti-drug trafficking measures. Using a process tracing method, it argues that Turkey's formerly lax approach to drug control was gradually replaced by stronger enforcement, to the point that nowadays Turkey seems to see itself as a champion of international police cooperation. The thesis then demonstrates that this change can only be partially explained by theories focusing on external change drivers, such as the Americanization of global law enforcement or the Europeanization of Turkey in its bid for EU membership. It argues that change is best explained by analysing micro-processes of socialization within the Turkish National Police (TNP), which reveal the role of domestic factors unexplainable otherwise, such as the importance of protecting the reputation of Turkey and of the TNP among international partners, and the importance of personal career-oriented behaviour by officers of the TNP.